THE MEMORISATION CURRICULA IN THE ISLAMIC EDUCATIONAL INSTITUTIONS - Yunita, Yunita; Baidi, Yasin; Muhajir, Muhajir (IAIN PONOROGO, 2023)
Pertanyaan apakah menghafal itu penting atau tidak akhir-akhir ini mendapat perhatian besar. Pakar pendidikan telah mengajukan berbagai argumen, baik yang mendukung maupun menentang, namun pendapat para pendidik Islam belum didengarkan. Dengan menelusuri perkembangan teknik hafalan di lembaga pendidikan Islam sejak masa Ottoman hingga saat ini di Indonesia, tulisan ini berupaya untuk mengatasi kesenjangan tersebut. Isu krusial kedua yang diangkat dari analisis literatur ini adalah terdepresiasinya penghafal Al-Qur'an akibat meningkatnya jumlah rumah tangga tahfidz di Indonesia belakangan ini. Ringkasnya, artikel ini mengemukakan tiga poin penting: Pertama, kurikulum pendidikan Islam kini memasukkan hafalan sebagai strategi pembelajaran dan akan selalu demikian. Kedua, menghafal tidak secara inheren mendiskualifikasi proses pemahaman. Pertentangan antara kedua konsep ini hanyalah salah satu contoh bagaimana cara berpikir kita dikaburkan oleh perbedaan ontologi sistem pendidikan Islam dan Eropa. Ketiga, cita-cita luhur seorang Muslim untuk mewujudkan Al-Qur'an dalam dirinya telah menjadi ciri khas lembaga pendidikan Islam selama berabad-abad dan terancam punah. Ketiga kesimpulan ini berkaitan dengan peningkatan setidaknya dua metodologi pengajaran dalam pendidikan Indonesia: kebutuhan untuk mempertahankan sistem pendidikan yang asli dari lembaga pendidikan Islam dan keberlanjutan tingkat pendidikan Islam.The question of whether memorizing things is essential or not has recently gained substantial attention. Education specialists have offered a range of arguments, both for and against, but Islamic educators' opinions have not been heard. By tracking the development of memorization techniques in Islamic educational institutions from the Ottoman era to the present day in Indonesia, this essay seeks to address this gap. The second crucial issue brought up by this literature analysis is the depreciation of memorizing the Qur'an as a result of the recent increase in tahfidz households in Indonesia. In summary, this article makes three crucial points: First, the Islamic educational curriculum now incorporates memorization as a learning strategy and always will. Second, memorization does not inherently disqualify the understanding process. The conflict between these two concepts is just one example of how our way of thinking is clouded by the divergent ontologies of the Islamic and European educational systems. Third, the lofty goal of a Muslim embodying the Qur'an inside himself or herself has been the hallmark of Islamic educational institutions for centuries and is in risk of disappearing. These three conclusions are pertinent to the promotion of at least two instructional methodologies in Indonesian education: the need to maintain an educational system that is native to the womb of Islamic educational institutions and the sustainability of Islamic educational levels.